A phase I/II study of oral clofarabine plus low‐dose cytarabine in previously treated acute myeloid leukaemia and high‐risk myelodysplastic syndrome patients at least 60 years of age. (8th April 2015) - Buckley, Sarah A.; Mawad, Raya; Gooley, Ted A.; Becker, Pamela S.; Sandhu, Vicky; Hendrie, Paul; Scott, Bart L.; Wood, Brent L.; Walter, Roland B.; Smith, Kelly; Dean, Carol; Estey, Elihu H.; et al.
Summary Outcomes for older adults with acute myeloid leukaemia (AML) and myelodysplastic syndrome (MDS) are generally poor, and new effective therapies are needed. We investigated oral clofarabine combined with low‐dose cytarabine (LDAC) in patients aged 60 years and above with relapsed or refractory AML or high‐risk MDS in a phase I/II trial. A 3 + 3 dose escalation of oral clofarabine was followed by a phase II expansion with the aim of obtaining a complete response (CR) rate ≥30%. We identified 20 mg/d for 5 d as the maximum tolerated dose (MTD) of oral clofarabine. A total of 35 patients, with a median age of 72 years, were treated. Of 26 patients enrolled at the MTD, 4 had treatment‐related grade 3–4 non‐haematological toxicities, but none died within 28 d. The observed CR rate and median survival were 34% [95% confidence interval (CI), 18–50%] and 6·8 months overall and 38% [95% CI, 19–57%] and 7·2 months at the MTD. The median disease‐free survival was 7·4 months. Fifty‐two percent (23/44) of cycles administered at the MTD were done without hospital admission. This combination of oral clofarabine and LDAC demonstrated efficacy with a CR rate of >30% and acceptable toxicity in older patients.